PENGARUH KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN - I Putu, Soni Pariascana; Ni Luh De Erik Trisnawati (STEKOM PRESS, 2022)
The purpose of this study was to determine the effect of organizational commitment and job satisfaction on the turnover intention of Alfamart employees in Sawan District. The analysis technique used in this research is validity and reliability test, classical assumption test, multiple linear regression analysis, t-test, analysis of determination and f-test test. The results showed that organizational commitment had an effect on the turnover intention of Alfamart employees in Sawan District. The results of hypothesis testing with the t-test showed that organizational commitment had a negative and significant effect on turnover intention. Job satisfaction has an effect on the turnover intention of Alfamart employees in Sawan District. The results of hypothesis testing with the t-test show that job satisfaction has a negative and significant effect on turnover intention. The results of the F test obtained that the F-count > F-table, (17.659 > 3.29), this indicates that the variables of organizational commitment and job satisfaction have a joint effect on turnover intention with a significant level of 0.000 < 0.050